2018
DOI: 10.3389/fonc.2018.00256
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Composition and Contribution of Tertiary Lymphoid Structures to Tumor Immune Infiltration and Modulation by Radiation Therapy

Abstract: Immune-based anti-cancer strategies combined with radiation therapy (RT) are actively being investigated but many questions remain, such as the ideal treatment scheme and whether a potent immune response can be generated both locally and systemically. In this context, tumor-associated tertiary lymphoid structures (TLS) have become a subject of research. While TLS are present in several types of cancer with strong similarities, they are especially relevant in medullary breast carcinoma (MBC). This suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
(32 reference statements)
4
22
0
Order By: Relevance
“…In a meta-analysis, CD3 + , CD8 + and the ratio of CD8 + /FOXP3 + TILs presented the most significant positive effect on survival (hazard ratio (HR): 0.59 (confidence interval (CI) 0.43–0.78; HR:0.71 (CI:0.62–0.82 and HR:0.48, CI:0.34–0.68, respectively) (55). The relevance of local lymphoid structures to support immune activation in response to RT has also been recently suggested by our group in medullary BC (56), a type of BC infiltrated with tertiary lymphoid structures (TLS). We showed acute and transient TLS depletion after hypo-fractionated RT, followed by a restoration phase and identified possible cellular targets (i.e., Tregs) that could be selectively modulated in subsequent studies to optimize anti-tumor immune response (56).…”
Section: Tumor-infiltrating Lymphocytes (Tils): a Biomarker Of Bc Immsupporting
confidence: 54%
See 1 more Smart Citation
“…In a meta-analysis, CD3 + , CD8 + and the ratio of CD8 + /FOXP3 + TILs presented the most significant positive effect on survival (hazard ratio (HR): 0.59 (confidence interval (CI) 0.43–0.78; HR:0.71 (CI:0.62–0.82 and HR:0.48, CI:0.34–0.68, respectively) (55). The relevance of local lymphoid structures to support immune activation in response to RT has also been recently suggested by our group in medullary BC (56), a type of BC infiltrated with tertiary lymphoid structures (TLS). We showed acute and transient TLS depletion after hypo-fractionated RT, followed by a restoration phase and identified possible cellular targets (i.e., Tregs) that could be selectively modulated in subsequent studies to optimize anti-tumor immune response (56).…”
Section: Tumor-infiltrating Lymphocytes (Tils): a Biomarker Of Bc Immsupporting
confidence: 54%
“…The relevance of local lymphoid structures to support immune activation in response to RT has also been recently suggested by our group in medullary BC (56), a type of BC infiltrated with tertiary lymphoid structures (TLS). We showed acute and transient TLS depletion after hypo-fractionated RT, followed by a restoration phase and identified possible cellular targets (i.e., Tregs) that could be selectively modulated in subsequent studies to optimize anti-tumor immune response (56).…”
Section: Tumor-infiltrating Lymphocytes (Tils): a Biomarker Of Bc Immsupporting
confidence: 54%
“…The effect of cancer therapies on TLSs and the resulting potential impact on patient clinical outcome have begun to be explored. In the Kras LSL−G12D/+ Trp53 −/− (KP) genetically engineered mouse model of lung cancer, hypo-fractionated radiotherapy induces an early reduction in TLS densities followed by their restoration within 2 weeks 119 . Two independent studies of human NSCLC reported that TLSs present in lesions regressing after neoadjuvant anti-PD1 therapy 30 or chemotherapy 120 were associated with longer disease-free survival and overall survival 120 .…”
Section: Therapeutic Modulation Of Tlss and Its Impact On Clinical Oumentioning
confidence: 99%
“…The reduction of the irradiated tissue volume would lead to the theoretical sparing of tumor-associated lymphocytes from the peri-tumoral TME, which can be rich in immune cells and can contain tertiary lymphoid structures ( 54 ). This sparing strategy could lead to a pro-immunogenic effect by sparing effector TILs which could otherwise be depleted following irradiation ( 54 ). It could also avoid the enhancement of proliferation and suppressive function of intra-tumoral T-reg, which has been shown following stereotactic irradiation ( 55 ).…”
Section: Controversies About Irradiated Target Volumesmentioning
confidence: 99%